ANALISIS KOMPARATIF TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI KARET DESA SUNGAI JALAU DENGAN DESA TERATAK KABUPATEN KAMPAR - Yusmini Yusmini; Shorea Khaswarina; Evy Maharani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
This study aims  to analyze the  rubber  farm income  and  household welfare level  comparison  of  farmers  in  Desa  Sungai  Jalau  and  Desa  Teratak.  The  results showed  net  income  and  labor  income off  arm families  during the  one-year  analysis of rubber,  a  rubber  farmer  Desa  Sungai  Jalau  net  income  of  Rp11,253,051.5/ha  and labor  income  families  Rp17,833,933.8/ha,  while  the  net  income  per  farmer  Desa Teratak  year  amounted  to  USD11,316,228.1/ha  and  labor  income  families Rp18,352,591.7/ha, net income and income of farming families working rubber farmer Desa Teratak  is greater  than  Desa Sungai Jalau  respectively  0.56% and  2.91%.  The average    of  rubber farmers in  Desa Sungai Jalau  and  Desa Teratak  is  welfare,  based on the  test  there were  significant  differences in  the level of  well-being  that  significant in the community Desa Sungai Jalau with Desa Teratak.